Comunicación y cyber periodismo: Caso Diario al dia de Babahoyo - Córdova Galárraga, Derek Oswaldo (2020)
The cyber journalism in Ecuador as in differents parts of the world is seen as an enriching source for those who practice the journalism proffesion, because they are the ones who are most familiar with the news thought social networks, web pages and digital newspapers. This is because some year ago the internet is the main source for communication and dissemination of content. The objetive of this project is to point out and analyze about the communication and cyber journalism in Ecuador, specifically in Babahoyo city, using the digital newspapers ALDÍA.COM as a case.